(untitled) (Research, Society and Development, 2022)
The mechanism of interaction among polyanions and Staphylococcal alpha hemolysin (αHL) ion channel still was not elucidated completely. The initial interaction of polyanions with surface membrane of phospholipids is based in Ca2+ bridge formation. Such interaction increases polyanion concentration close to membrane surface that, in turn, increases the probability of polyanion enter into a channel and blocks it. Thus, this study proposed to investigate the role of the lipid membrane composition on interaction of polyanions, such as heparin, with αHL channel. It was found that the effectiveness of heparin to block αHL channels was significantly dependent on the lipid composition of the bilayers. The lipids on their ability to support heparin influence were ranked as follows: PC >> PI » PS > DPhPS ³ PE ³ DPhPC > OChol. These results indicate that the interaction of Ca2+ with lipid membranes depends on the exposure and density of phosphate groups in phospholipids at membrane surface. On the other hand, the effectiveness of heparin to block αHL channel was more strongly correlated with the length of the hydrocarbons chain of fatty acids of the phospholipids. Thus, we demonstrate that the polar head group of phospholipids in the membranes affects their interaction with divalent ions by changing their surface potential, and therefore influences the effectiveness of heparin blockage in the formed channels. The results might be of interest for pharmacology, biomedicine, and research aiming to design mesoscopic pore blockers.